Heart Failure Caregiver Burden and Outcomes: A Systematic Review - Wanich Suksatan; Thitipong Tankumpuan; Patricia M. Davidson (SAGE Publishing, 2022)
Introduction/Objective: This review aimed to summarize articles describing caregiver burden and the relationship between health outcomes as well as describing interventions focusing on this population. Methods: The review used the PRISMA statement and Whittemore and Knafl guidelines. The search engines Scopus, PubMed, Ovid (PsycINFO), and CINAHL were searched for articles published in English. Results: This review included 30 studies that met the criteria. Physical, psychological, and social factors were associated with HF caregiver burden. HF caregiver interventions included health education, post-discharge home visits, phone calls, counseling, and support groups that demonstrated some potential to reduce the caregivers' burden. Discussion: Healthcare provider team should screen for caregiver burden and promote healthy behaviors, and strategies to improve quality of life. Further studies should include caregivers as care team members and embed social networking in the interventions for reducing HF caregiver burden. The caregivers' burden could influence the poor outcomes of care, including physical, psychological, societal, and functional dimensions. Future interventions should develop to alleviate HF caregiver burden.